Allergic Rhinitis in Ghana: Knowledge, Prevention, and Management Among Community Residents - Opoku, Oscar Agyemang; Opoku Agyemang, Cecilia; Nyarko Mensah, Olivia; Opoku, Albert; Agyenim Boateng, Linda; Kwakye, Shadrack (Journal of Applied Nursing and Health, 2025)
Background: Allergic rhinitis is a common comorbidity associated with respiratory illnesses, including asthma, sinusitis, and otitis media with effusion, and significantly impacts patients’ quality of life. This study aimed to assess the knowledge, preventive practices, and management of allergic rhinitis among residents of Santasi-Apire in the Ashanti Region, Ghana. Methods: A descriptive cross-sectional study was conducted using a quantitative approach. The target population consisted of individuals aged 15 years and above residing in Santasi-Apire. A total of 100 participants were recruited through convenience sampling. The inclusion criteria included permanent residents aged 15 years or older; individuals with cognitive impairments or those who declined consent were excluded. Data were collected using a structured questionnaire based on the study objectives, which covered variables such as knowledge, preventive measures, and management practices related to allergic rhinitis. Ethical approval was obtained from the Kumasi Metropolitan Health Directorate. Data were analyzed using SPSS version 20.0, with results presented as frequencies and percentages. Results: A total of 48% of respondents misidentified allergic rhinitis as a common cold. Dust was identified as the most prevalent trigger (70%), followed by perfume (22%), pollen (5%), hay (3%), certain foods (3%), and specific drugs (2%). About 65% of participants reported avoiding dusty environments and smoke, while 15% did not engage in any preventive behavior. Sprinkling water on roads to reduce dust was the most commonly practiced preventive measure (52%). In terms of management, 47% used antihistamines, and 39% relied on over-the-counter medications. A minority (2%) reported no form of management. Conclusion:  The study indicates that dust is the primary trigger of allergic rhinitis among Santasi-Apire residents, who predominantly experience rhinorrhea as a symptom. While community members recognize allergic rhinitis as a serious condition, their efforts to prevent and manage it largely rely on environmental control and self-medication. Strengthening public health education on evidence-based management and clinical evaluation is recommended.